2019
DOI: 10.3390/pharmaceutics11120666
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and Polymer Excipients Enhance Uptake and Splice-Switching Activity of Peptide-Dendrimer/Lipid/Oligonucleotide Formulations

Abstract: Non-viral transfection vectors are commonly used for oligonucleotide (ON) delivery but face many challenges before reaching the desired compartments inside cells. With the support of additional compounds, it might be more feasible for a vector to endure the barriers and achieve efficient delivery. In this report, we screened 18 different excipients and evaluated their effect on the performance of peptide dendrimer/lipid vector to deliver single-stranded, splice-switching ONs under serum conditions. Transfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Luciferase-based assays are frequently used, and considered one of valuable tools to test efficacy of splice-switching ON delivery [ 38 , 39 ]. We have previously utilized such an assay to establish a robust and reliable approach to test the efficacy of a large number of transfection reagents to deliver splice-switching ON [ 32 , 40 ]. The procedure of complex formation was performed according to Saher et al with some modifications [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Luciferase-based assays are frequently used, and considered one of valuable tools to test efficacy of splice-switching ON delivery [ 38 , 39 ]. We have previously utilized such an assay to establish a robust and reliable approach to test the efficacy of a large number of transfection reagents to deliver splice-switching ON [ 32 , 40 ]. The procedure of complex formation was performed according to Saher et al with some modifications [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also a good candidate as drug delivery system for small molecules and macromolecular gene therapeutics [ 46 , 47 , 48 ]. Previously, we demonstrated that transfection efficiency of peptide dendrimers/lipids can be further improved by adding different types of saccharides or polyol compounds [ 40 ]. Among those screened polymeric excipients, PVA18 was one of the best excipients to enhance transfection efficiency of peptide dendrimer/lipid hybrids [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations